PENGARUH MOTIVASI BELAJAR DAN KREATIVITAS TERHADAP PRESTASI BELAJAR YANG DIMODERASI ARTIFICIAL INTELLIGENCE (AI) PADA MAHASISWA FEB UNISSULA - Anggun Hemalia Putri; Nurhidayati Nurhidayati (RJABM (Research Journal of Accounting and Business Management), 2026)
This study aims to analyze the effect of learning motivation and creativity on students’ academic achievement at the Faculty of Economics and Business, Sultan Agung Islamic University, with Artificial Intelligence (AI) as a moderating variable. The research background stems from the growing use of AI in education, which presents both opportunities and challenges for students’ motivation, creativity, and learning outcomes. A quantitative explanatory method was employed with a sample of 100 students from the 2022–2024 cohorts, determined using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression and moderation interaction tests with SPSS. The results reveal that learning motivation and creativity have a positive and significant effect on academic achievement. However, AI does not act as a moderating variable but has a direct positive influence on academic achievement. Overall, the findings emphasize the importance of enhancing motivation and creativity while utilizing AI wisely to support academic success in the digital era.